2020
DOI: 10.3390/v12090951
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Rice Reveals the lncRNA–mRNA Regulatory Network in Response to Rice Black-Streaked Dwarf Virus Infection

Abstract: The plant genome can produce long non-coding RNAs (lncRNAs), some of which have been identified as important regulators of gene expression. To better understand the response mechanism of rice plants to Rice black-streaked dwarf virus (RBSDV) infection, we performed a comparative transcriptome analysis between the RBSDV-infected and non-infected rice plants. A total of 1342 mRNAs and 22 lncRNAs were identified to be differentially expressed after RBSDV infection. Most differentially expressed transcripts involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 58 publications
(87 reference statements)
0
23
0
Order By: Relevance
“… Kwenda et al (2016) genome-wide identified potato lincRNAs and functionally analyzed the mechanism in response to Pectobacterium carotovorum subspecies brasiliense infection. A total of 1342 mRNAs and 22 lncRNAs of rice were identified to be differentially expressed after RBSDV infection ( Zhang et al, 2020 ). An lncRNA of rice, ALEX1, whose expression is highly induced by Xoo infection, can active the JA pathway and promote resistance to bacterial blight ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… Kwenda et al (2016) genome-wide identified potato lincRNAs and functionally analyzed the mechanism in response to Pectobacterium carotovorum subspecies brasiliense infection. A total of 1342 mRNAs and 22 lncRNAs of rice were identified to be differentially expressed after RBSDV infection ( Zhang et al, 2020 ). An lncRNA of rice, ALEX1, whose expression is highly induced by Xoo infection, can active the JA pathway and promote resistance to bacterial blight ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…During RBSDV infection, The up-regulated rice signal transductionassociated genes can improve rice resistance by inducting of the jasmonic acid (JA) pathway and inhibiting the abscisic acid (ABA) pathway [12,13]. Recently reports shown that in addition to resistance genes, non-coding RNAs (ncRNAs) including small ncRNAs and long ncRNAs (lncRNAs) also play an important in rice defense against pathogens [14,15]. Although many works associated with functional characterization of small ncRNAs are reported, the function of lncRNAs in plants is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lncRNAs involved in resistance regulatory mechanisms against pathogens are rarely reported, especially in rice [33,34]. Tianze et al revealed the regulatory network between lncRNA and mRNA in rice response to RBSDV infection by performing RNA-seq [35]. To date, the expression pro le and functional characterization of lncRNAs during RSV and RBSDV infection in rice are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Three groups addressed the roles of non-coding RNAs in plant virus infections [5][6][7]. Liu and colleagues used microarray analysis to screen microRNAs (the microRNAome) and obtained a global profile allowing for the identification of some miRNAs and their roles as well as their corresponding target mRNAs, and resulting defense signaling pathways in beet necrotic yellow vein virus pathogenesis in Nicotiana benthamiana plants [6].…”
mentioning
confidence: 99%
“…Suppression of nbe-miR1919c-5p by STTM resulted in increased titers for TbCSV and TbCSB, plus more severe symptoms, including leaf curling in plants. Zhang and colleagues assessed the network of differentially expressed long non-coding RNAs (lncRNAs, >200 nt) and mRNAs in rice plants infected with rice black-streaked dwarf virus (RBSDV) [7]. The biological roles of lncRNAs are largely still unknown.…”
mentioning
confidence: 99%